Muhammad Ibnu Yusuf Al Jazari: Sumbangan Beliau Dalam Bidang Hadith - Muhammad Zubair Bin Md Sa; Khairul Anuar Mohamad; Mohd Nor Adzhar Ibrahim (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024